Diffuse oesophageal spasm: diagnosis by ambulatory 24 hour manometry. Issue 2 (1st August 1997) - Barham, C P; Gotley, D C; Fowler, A; Mills, A; Alderson, D
Abstract : Background —Diffuse oesophageal spasm (DOS) is a potential cause of intermittent chest pain and/or dysphagia. In the past, the diagnosis of DOS has relied on criteria obtained from standard oesophageal manometry (more than one simultaneous contraction in a series of 10 wet swallows with the rest being peristaltic). As symptoms are intermittent, however, 24 hour manometry may well be more suited to its investigation. Aims —To determine the ability of 24 hour manometry to detect the symptomatic contractions of DOS and to compare standard, laboratory based manometry with 24 hour manometry in its diagnosis. Patients —Three hundred and ninety consecutive patients referred with suspected oesophageal disorders. Methods —Standard laboratory based manometry and 24 hour outpatient manometry. Results —Sixteen patients were classified by 24 hour manometry as having DOS on the basis of painful contractions (spasms) of excessive duration and increased amplitude. Laboratory based manometry failed to detect the majority of these patients with DOS (14/16), and 53/55 were incorrectly labelled as having DOS on the basis of asymptomatic manometric findings. Conclusion —The detection of symptomatic DOS requires 24 hour manometry.